Women's Work in Response to Urbanization: Evidence from Odisha. Issue 1 (June 2019) - Mitra, Arup
This article examines the impact of urbanization as a vehicle of modernization on a variable like women workforce participation rate (WFPR), which is highly sensitive to social and cultural factors. Based on district level data, urbanization and women work participation are seen to have a negative association both in the rural and urban areas, although, ideally speaking, urbanization is expected to raise work opportunities. Owing to compulsions, women from poor households participate in the labour market which may result in a positive relationship between poverty and female work participation rate. Further, economic growth and WFPR unravel a negative association which is indicative of either a backward sloping supply curve of women at higher levels of per capita income or growth being non-inclusive and unable to create work opportunities. The lack of jobs of desirable status for a long time in turn leads to the phenomenon of 'discouraged dropouts'. It is important to counter such distortions through policy interventions so that women are able to access higher levels of skill and education and subsequently participate in the job market instead of withdrawing.